Uniqueness of tree stand composition and soil microbial communities are related across urban spruce-dominated forests - Korhonen, Aku; Katavisto, Oskar; Adamczyk, Sylwia; Adamczyk, Bartosz; Hamberg, Leena (Springer Nature, 2024)
Context: Urban forest soils represent significant reservoirs of biodiversity in cities. Retaining this diversity under urban land-use change requires understanding on how species richness, community assembly and uniqueness of species assemblages are related to local forest characteristics and surrounding landscape structure. Objectives: Our aim was to assess the significance and relative importance of logging history, tree species composition and urbanization in shaping soil microbial communities across urban spruce-dominated forest landscapes. We investigated responses of microbial diversity from three complementary viewpoints: local diversity, community assembly patterns and community uniqueness. Methods: We collected soil bacterial and fungal metabarcoding data from 73 spruce-dominated forest sites distributed in three urban centers across southern Finland. We related these data to measurements of logging intensity, tree species composition and degree of urbanization. Results: Logging intensity, tree species composition and urbanization affected site-scale microbial diversity, but the effects varied between microbial groups. Only logging intensity had a significant imprint on microbial assembly, and this effect was restricted to bacteria. Relative uniqueness of microbial assemblages at the landscape-scale was coupled with the uniqueness of tree species composition in all microbial groups, and further affected by tree diversity in saprotrophic fungi and urbanization in ectomycorrhizal fungi. Conclusions: In the context of urban spruce-dominated forests, locally diverse tree stands are not necessarily the same as those that contribute the most to landscape-scale diversity. Identifying and preserving contrasting tree stand structures, which support distinctive soil microbial assemblages, may be the winning strategy in maintaining a wide range of soil microbial diversity.
Keywords: urban forestry; fungi; bacteria; metabarcoding; biodiversity